The Impact of Positive Resection Margins on Survival and Recurrence Following Resection and Adjuvant Chemotherapy for Pancreatic Ductal Adenocarcinoma. Issue 3 (March 2019) - Ghaneh, Paula; Kleeff, Jorg; Halloran, Christopher M.; Raraty, Michael; Jackson, Richard; Melling, James; Jones, Owain; Palmer, Daniel H.; Cox, Trevor F.; Smith, Chloe J.; O'Reilly, Derek A.; Izbicki, Jakob R.; et al.
Abstract : Objective and Background: Local and distant disease recurrence are frequently observed following pancreatic cancer resection, but an improved understanding of resection margin assessment is required to aid tailored therapies. Methods: Analyses were carried out to assess the association between clinical characteristics and margin involvement as well as the effects of individual margin involvement on site of recurrence and overall and recurrence-free survival using individual patient data from the European Study Group for Pancreatic Cancer (ESPAC)-3 randomized controlled trial. Results: There were 1151 patients, of whom 505 (43.9%) had an R1 resection. The median and 95% confidence interval (CI) overall survival was 24.9 (22.9–27.2) months for 646 (56.1%) patients with resection margin negative (R0 >1 mm) tumors, 25.4 (21.6–30.4) months for 146 (12.7%) patients with R1<1 mm positive resection margins, and 18.7 (17.2–21.1) months for 359 (31.2%) patients with R1-direct positive margins ( P < 0.001). In multivariable analysis, overall R1-direct tumor margins, poor tumor differentiation, positive lymph node status, WHO performance status ≥1, maximum tumor size, and R1-direct posterior resection margin were all independently significantly associated with reduced overall and recurrence-free survival. Competing risks analysis showed that overall R1-direct positive resection margin status, positive lymph node status, WHO performance status 1, and R1-direct positive superior mesenteric/medial margin resection status were all significantly associated with local recurrence. Conclusions: R1-direct resections were associated with significantly reduced overall and recurrence-free survival following pancreatic cancer resection. Resection margin involvement was also associated with an increased risk for local recurrence. Abstract : Supplemental Digital Content is available in the text